Women and Gender Equality in Higher Education? - Miriam E. David (MDPI AG, 2015)
I look at the changes in higher education (HE) and women's lives over the last 50 years, drawing on my recent book Feminism, Gender & Universities: Politics, Passion & Pedagogies which is a life history of feminism entering academe. The Robbins Report (cmnd 2154 1963) on HE was published in the same year that I went to university. It inaugurated a process of change and educational expansion that was linked to other major social transformations, including feminism. Its effects have been widely felt such that women now participate in education and employment on unprecedented levels. Indeed, it has opened up opportunities for education and employment for women including individual and social mobility. From my study I show how it opened up opportunities for women from both middle class and working class backgrounds to be first-in-the-family to go to university. I will also argue that whilst there have been very welcome changes in education, and HE especially, such that there is a gender balance of undergraduate students in HE, this does not mean that gender equality has been achieved. Patriarchy or hegemonic masculinity in HE is still strongly felt and experienced despite women's and feminist involvements in academe over the last 50 years. The question remains about how to transform universities to achieve genuine gender equality across all students and academics in HE.